Microvariation in the old Italo-Romance left periphery. The case of si - Wolfe, S (Editura Academiei Române, 2021)
This article presents a novel analysis of four Old ItaloRomance texts to better understand the syntax of the particle SI. The proposal is that the variation attested can be understood in a model where SI is understood to be merged in distinct positions in the Old Italo-Romance left periphery. Furthermore, it is suggested that the distribution of SI may depend on the types of constituents that can act as satisfiers of the V2 constraint in a given language.